Immune checkpoint inhibitors in advanced upper and lower tract urothelial carcinoma: a comparison of outcomes. (8th February 2021) - Esagian, Stepan M.; Khaki, Ali Raza; Diamantopoulos, Leonidas N.; Carril‐Ajuria, Lucia; Castellano, Daniel; De Kouchkovsky, Ivan; Park, Joseph J.; Alva, Ajjai; Bilen, Mehmet A.; Stewart, Tyler F.; McKay, Rana R.; Santos, Victor S.; et al.
Abstract : Objectives: To compare clinical outcomes between patients with locally advanced (unresectable) or metastatic urothelial carcinoma (aUC) in the upper and lower urinary tract receiving immune checkpoint inhibitors (ICIs). Patients and Methods: We performed a retrospective cohort study collecting clinicopathological, treatment, and outcome data for patients with aUC receiving ICIs from 2013 to 2020 across 24 institutions. We compared the objective response rate (ORR), overall survival (OS), and progression‐free survival (PFS) between patients with upper and lower tract UC (UTUC, LTUC). Uni‐ and multivariable logistic and Cox regression were used to assess the effect of UTUC on ORR, OS, and PFS. Subgroup analyses were performed stratified based on histology (pure, mixed) and line of treatment (first line, subsequent line). Results: Out of a total of 746 eligible patients, 707, 717, and 738 were included in the ORR, OS, and PFS analyses, respectively. Our results did not contradict the hypothesis that patients with UTUC and LTUC had similar ORRs (24% vs 28%; adjusted odds ratio [aOR] 0.73, 95% confidence interval [CI] 0.43–1.24), OS (median 9.8 vs 9.6 months; adjusted hazard ratio [aHR] 0.93, 95% CI 0.73–1.19), and PFS (median 4.3 vs 4.1 months; aHR 1.01, 95% CI 0.81–1.27). Patients with mixed‐histology UTUC had a significantly lower ORR and shorter PFS vs mixed‐histology LTUC (aOR 0.20, 95% CI 0.05–0.91 and aHR 1.66, 95% CI 1.06–2.59), respectively). Conclusion: Overall, patients with UTUC and LTUC receiving ICIs have comparable treatment response and outcomes. Subgroup analyses based on histology showed that those with mixed‐histology UTUC had a lower ORR and shorter PFS compared to mixed‐histology LTUC. Further studies and evaluation of molecular biomarkers can help refine patient selection for immunotherapy.